Compliance with National Institute of Health and Care Excellence risk-based screening for Gestational Diabetes Mellitus in nulliparous women. (April 2016) - Murphy, Nicolai M.; McCarthy, Fergus P.; Khashan, Ali S.; Myers, Jenny E.; Simpson, Nigel A.B.; Kearney, Patricia M.; Greene, Richard A.; Poston, Lucilla; Kenny, Louise C.
Abstract: Objective: To investigate compliance with risk-based screening for Gestational Diabetes Mellitus (GDM) in a nulliparous cohort. Design: A retrospective analysis of nulliparous women recruited to a prospective cohort, the Screening for Pregnancy Endpoints (SCOPE) study, was performed. Population included 2428 healthy nulliparous women with singleton pregnancies, recruited within Cork, Ireland; and Manchester, Leeds and London, United Kingdom. Compliance with risk factor screening for GDM was assessed in relation to the following risk factors: obesity, family history of diabetes and increased ethnic risk. GDM was diagnosed using an oral Glucose Tolerance Test (GTT) with locally employed diagnostic criteria. Statistical analysis was performed using Statistical Packages for Social Sciences (SPSS V22). Descriptive statistics are presented for the various baseline characteristics using numbers and percentages. Cross tabulation was used to compare relevant groups. When comparing group distributions Chi-square test was used. p -value <0.05 was considered statistically significant. Results: In the entire cohort of 2432 women, 27% (650 Women) had one or more identifiable risk factors as defined by National Institute of Health and Care Excellence (NICE) for GDM. Of those that had identifiable GDM risk factors according to the NICE guidelines, 395(60.8%) were appropriately screened. 253 (38.9%) had risk factors but were not screened. 261 (14.6%) had no GDM NICE risk factors but were screened with an oral GTT. Women with a risk factor that were screened with a GTT had an 8.9% ( n = 34) prevalence of GDM. Of those that were screened but did not have a risk factor 7.7% ( n = 20) were diagnosed with GDM. Overall, 2% (54 women) of the cohort had a diagnosis of GDM. Ethnicity was the risk factor most likely to be missed ( n = 55, 66.3%). The GTT test was completed within the recommended gestational window (24−28 weeks) 56.6% ( n = 371) of the time. Conclusion: This study highlights poor compliance with risk factor screening for GDM in nulliparous women. Further investigation into the underlying reasons is warranted as well as the implications for pregnancy outcome. Trial registration number: ACTRN12607000551493.